Implementasi Model Pembelajaran Write Around Pada Mata Pelajaran Fiqih Di MTs Nurul Hasanah Walbarokah - Melati, Rima; Nasution, Mawaddah (Yayasan Rahmat Islamiyah, 2024)
The write-around learning model is a type of cooperative learning where each group member can write a conclusion based on an image presented. Students can hone how to think quickly, write a story, and practice concluding the pictures presented. This research uses qualitative research with a case study approach. Data was collected using participatory observation and interviews with teachers in the field of study. Based on the results of research and discussion, it can be concluded that students can tell and write a picture that is presented.